Effect of Light Treatment on Chemical Composition of Andrographis paniculata Seedlings - Jiang, Zhehui; Wang, Tianhao; Zhang, Kaixue; Zhang, Meiqi; Ma, Ling; Ren, Weichao; Bao, Yihong; Ma, Wei (Frontiers in Chemistry, 2022)
The light quality consists of the spectrum of different bands, which not only affects plant, development and primary metabolism, but also affects the secondary metabolism of plants. It is an important factor affecting the content of active components of medicinal plants. The Andrographis paniculata seedlings planted in the lab, as materials, were tested with red light, far red light, blue light and ultraviolet light separately. The study assays the content of 6 chemical components (Ap、Neo、30、S3、S4、S7) separately by LC-MS, observes the changes of the content, and analyzes the relationship between the light quality and the active ingredient of Andrographis paniculata. By establishing he ointment yield and pH value, the fingerprint analysis method of Andrographis paniculata standard decoction, we discussed the selection of index components of Andrographis paniculata standard decoction, and it was suggested to select andrographolide as the index component. It will provide theoretical basis for the large area cultivation of Andrographis paniculata and optimizing the quality of medicinal materials to ensure the quality of standard decoction.